PERANCANGAN SISTEM INFORMASI PENGARSIPAN SURAT BERBASIS WEB DI SMK N 1 MUARO JAMBI (STUDI KASUS PENGOLAHAN DATA ARSIP): Filing Application;Incoming Mail;Outgoing Mail;Web;MySQL;PHP - Huda Aminuddin, Fattachul; Arjansyah, Arnol (LP2M Universitas Nurdin Hamzah, 2022)
Letters are one of the most important communication media in an agency, school or other form of organization, both to communicate with parties externally and internally. The purpose of this study is to find the right solution so that archiving incoming and outgoing mail at SMK Negeri 1 Muaro Jambi is more effective and efficient by creating an application for archiving incoming and outgoing letters. Making and developing applications using a static programming language, namely PHP (Hypertext Pre-processor) and MySQL as the application database. The results of the research on making incoming and outgoing mail filing applications are very helpful and make it easier for SMK Negeri 1 Muaro Jambi in archiving incoming and outgoing letters, especially the Administration section because the filing of letters is already stored in the database.